Chapter I servizi ecosistemici nella riproduzione dei sistemi territoriali. Osservazioni da una ricerca sugli scambi montagna-città - Dematteis, Giuseppe (Territori, 2020)
From a research for the Metropolitan City of Turin on the flows of matter, energy, services, people and information between the metro-mountain and metro-urban subsystems, it has emerged that the ecosystem flows always have a degree of openness to the outside, which requires an assessment of the positive or negative effects on ecosystems on a larger scale, up to the global one. In perspective, less sectoral and more multifunctional visions of the interventions seem to be required, which also recognize the mountain as a new central location as a privileged place to experiment with alternative life models.